2018
DOI: 10.1371/journal.pone.0199360
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculin skin test and QuantiFERON-Gold In Tube assay for diagnosis of latent TB infection among household contacts of pulmonary TB patients in high TB burden setting

Abstract: BackgroundWorld Health Organization (WHO) recommends systematic screening of high-risk populations, including household contacts (HHCs) of adult pulmonary tuberculosis (TB) patients, as a key strategy for elimination of TB. QuantiFERON-TB Gold In-Tube (QFT-GIT) assay and tuberculin skin test (TST) are two commonly used tools for the detection of latent tuberculosis infection (LTBI) but may yield differential results, affecting eligibility for TB preventive therapy.Materials and methodsA prospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 23 publications
4
30
1
Order By: Relevance
“…Although BCG is known to produce false positive TST results, the effect is minimal after 10 years of age [ 26 ]. Further, 75% of HHCs had TST ≥ 10 mm compared with 53% of IGRA ≥ 0.35 UI/ml which is consistent with other household contact studies in developing countries whereas TST often yields more positive results compared with IGRA [ 27 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…Although BCG is known to produce false positive TST results, the effect is minimal after 10 years of age [ 26 ]. Further, 75% of HHCs had TST ≥ 10 mm compared with 53% of IGRA ≥ 0.35 UI/ml which is consistent with other household contact studies in developing countries whereas TST often yields more positive results compared with IGRA [ 27 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…In high‐burden settings and areas in which BCG vaccination is ubiquitous, the accuracy of the tuberculin skin test for the diagnosis of tuberculosis infection is controversial . TST and QFT test concordance test was poor, which was same as other regions with highest TB burden, where BCG are administered . In addition, our project site (Danyang county of Jiangsu province) is located close to the sea where nontuberculous Mycobacterium is highly prevalent.…”
Section: Discussionmentioning
confidence: 97%
“…21,28 TST and QFT test concordance test was poor, which was same as other regions with highest TB burden, where BCG are administered. [29][30][31][32][33][34] In addition, our project site (Danyang county of Jiangsu province) is located close to the sea where nontuberculous Mycobacterium is highly prevalent. In prior work from our province, we have shown that the prevalence of nontuberculous Mycobacterium is high.…”
Section: Discussionmentioning
confidence: 99%
“…The two main tests in use (TST and IGRAs) both measure the immunological response to MTB antigens. TST is inexpensive but logistically challenging for patients and health care staff, different results may be obtained depending on which purified protein derivative products are used [37] and there continue to be widespread shortages of quality-assured tuberculin in many low-and middle-income countries [38]. IGRAs are more specific than TST and only one clinic visit is required by the patient for a venous blood sample.…”
Section: Diagnosis Of Ltbimentioning
confidence: 99%